Starfruit (Averrhoa carambola L.) jam enriched with different types of sugar: A comparative study - Apolonio, K B M (Plant Science Today, 2025)
This study used an experimental research design. The study was conducted to develop food products using starfruit as the main ingredient and to determine the nutritional composition of starfruit jam. Fifty respondents evaluated the starfruit jam through organoleptic criteria such as appearance, aroma, flavor, consistency, taste, aftertaste, and overall acceptability; a 9-point hedonic scale was used to determine the level of acceptability. This study included three treatments using varying types of sugar, such as white (treatment 1), brown (treatment 2), and muscovado (treatment 3), with the same measurements of ingredients generally acceptable as a result. Treatment 2 has the highest overall acceptability, followed by Treatment 3, and the least is Treatment 1, which are all described as very much by the respondents. Additionally, treatment 2 is the most preferred product regarding taste and aftertaste, while the different age groups have diverse acceptability levels when the food product was evaluated. Starfruit jam was analyzed, and its various nutritional content was determined to ensure that it is healthy and nutritious when consumed. Furthermore, the economic value of starfruit jam provides high investment returns due to the province's availability and affordability of supply. Finally, a potential source of income and product commercialization was forecasted for this newly developed foodstuff.